Distribution of Pasteurella multocida B:2 in the respiratory, gastrointestinal and urinary tracts of buffaloes following experimental subcutaneous inoculation - S., Annas; Zamri-Saad, M.; M. S., Abubakar; F. F. A., Jesse; Z., Zunita (Hilaris Publishing, 2014)
Pasteurella multocida B:2 causes haemorrhagic septicaemia (HS) in cattle and buffalo, leading to acute death of many animals, usually in the form of outbreaks. HS occurs especially in Asia and Africa, leading to devastating loss of animals and economics. The involvement of respiratory tract as the route of infection and transmission has been well established. The present study describes the distribution of P. multocida B:2 using bacteriological isolations in the respiratory, gastrointestinal and urinary tracts of buffalo calves following different dosages of subcutaneous exposure to live wild-type P. multocida B:2. Nine buffalo calves were divided into 3 groups before calves of Group 1 were inoculated subcutaneously with 109 cfu/ml of live wild-type P. multocida B:2. Calves of Group 2 were similarly inoculated with 105 cfu/ml while calves of Group 3 were exposed to PBS. All calves of Group 1 were euthanised between 6 and 12 h post-infection, while calves Group 2 were euthanized between 24 and 48 h post-infection. P. multocida B:2 was isolated from the lungs, liver, deodenum, rectum, urinary bladder swabs and the urine of all infected calves of Groups 1 and 2. Bacterial concentration varied between the organs with the lungs showed significantly (p<0.05) higher concentration than other tracts. Nevertheless, duodenum, colon, liver and urinary bladder of infected calves showed considerably high concentrations of P. multocida B: 2. Both infected groups showed similar concentrations of P. multocida B:2 in the respiratory, gastrointestinal and urinary tracts. Isolation and detection of P. multocida B:2 in the gastrointestinal and urinary tracts of infected calves re-emphasize the role of these tracts in transmission of haemorrhagic septicaemia and aid in understanding the terminal stage of bacteraemia in HS.